(untitled) (Global Journals of Research in Engineering, 2023)
The article examines the effect of discrete basalt fiber and hybrid mixture on the tribotechnical properties of the organosilicon binder It was established that basalt plastic with a fiber content of 40-50 mass is characterized by the highest wear resistance index but by high values of the coefficient of friction and temperature in the contact zone The high indicators of the latter can be explained by the friction of the basalt fiber Hidden crystal graphite was added to the composition of basalt plastic to reduce the coefficient of friction and temperature in the contact zone As a result of the conducted research it was established that the best complex of tribological properties is characterized by a hybrid composite containing 35 mass of basalt fiber and 35 mass of hidden crystalline graphite